Analysis of the Influence of Competence, Work Attitude, and Incentives on Employee Performance at the North Labuhanbatu Regency Education Office - Sari, Maulyna; Siregar, Nasan Martua; Nasution, Ainul Khotimah; Lubis, Ismayani; Siahaan, Hendra; Yusrita, Yusrita (Journal of Finance and Business Digital, 2024)
This study aims to analyze the influence of competence, work attitude, and incentives on employee performance at the North Labuhanbatu Regency Education Office. The research method used a quantitative approach with a questionnaire distributed to 100 respondents. The results of regression analysis show that competence, work attitude, and incentives have a positive and significant influence on employee performance, both partially and simultaneously. Competence has the greatest influence, followed by incentives and work attitudes. The value of the determination coefficient (R²) of 67.8% indicates that these variables explain most of the variations in employee performance. This research suggests the importance of increasing competence, incentives, and positive work attitudes to support optimal employee performance.